RANCANG BANGUN ANTENA Yagi-LPDA PADA FREKUENSI 162 MHz UNTUK AIS PADA KAPAL LAUT DI PERAIRAN PULAU BALI - Putu Okta Hadi Saputra; I Putu Ardana; Nyoman Pramaita (Program Studi Teknik Elektro UNUD, 2023)
The role of the sea is very important as unifying the nation and the territory of Indonesia and consequently the Government is obliged to administer governance in the field of law enforcement both against threats of violations against the use of waters and to maintain and create shipping safety and security. One way to increase the ability of the apparatus and the government to monitor and secure the territory of the Unitary State of the Republic of Indonesia is to use the AIS (Automatic Identification System) system. This AIS is used to monitor the movement of ships and provide or receive information so that actions that can harm the Unitary State of the Republic of Indonesia can be prevented. Currently, ships in Indonesia are equipped with radar, but the scope of the radar emitted by Indonesian ships is still small and small. To overcome these problems the author wants to develop a thesis with the title